The Lost plays of Greek tragedy, Volume 1 neglected authors - Wright, Matthew (London Bloomsbury Academic, 2016)
"Matthew Wright offers an authoritative two-volume critical introduction and guide to the lost tragedies. This first volume examines the remains of works by playwrights such as Phrynichus, Agathon, Neophron, Critias, Astydamas, Chaeremon, and many others who have been forgotten or neglected. (Volume 2 explores the lost works of Aeschylus, Sophocles and Euripides.)" -- Publisher's website.
Volume 1. Neglected authors: The earliest tragedies -- Some fifth-century tragedians -- Agathon -- Tragic family trees -- Some fourth-century tragedians -- The very lost.
Includes bibliographical references and index.
Keywords: Greek drama (Tragedy) -- History and criticism; Lost literature -- Greece